Adopting a systems thinking approach to investigate the implementation and provision of a pharmacist-led post-discharge domiciliary medicines review service - Hamde Nazar (1733509) (2021)
Background Intervention planners need to be sufficiently cognisant of the health system landscape to facilitate embedding, adoption and diffusion of new services. Pharmacist-led transfer of care initiatives from hospital to community have been developed to address a health system flaw: patient hospital readmissions. A hospital in England partnered with a chain of community pharmacies establishing a domiciliary pharmacist medicines use review service (DMRS) for discharged patients to reduce hospital readmissions. Objectives We adopt a systems thinking approach to understand the adoption and diffusion of the service by investigating the perceptions of hospital and community pharmacy staff. The experience of a role swap between these settings is investigated to probe further system factors influencing service provision. Methods Semi-structured interviews informed by a conceptual model for the diffusion, dissemination and implementation of innovations, were conducted with hospital and community pharmacy staff between Oct–Dec 2016. Interviews were audio-recorded with consent, transcribed verbatim and a combination of inductive and deductive thematic analysis was used. Results Four each of hospital and community pharmacy staff were interviewed and four hospital staff were interviewed after the role swap. Staff indicated barriers and facilitators thematically related to organisational and individual-level components of a conceptual model about service diffusion and implementation. The role swap appeared to address the lack of a feedback loop, which was limiting engagement of hospital staff. The role swap led to improved trust and shared goals between the healthcare sectors and increased appreciation and self-efficacy of the hospital staff role. Conclusions A systems thinking lens offered the opportunity to investigate the wider healthcare system within which the DMRS was being provided. The role swap aligned to the principles of participatory design of an intervention to facilitate successful adoption and diffusion and contribute to more insightful evaluation about the process and context of service implementation. Other Information Published in: Research in Social and Administrative Pharmacy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.sapharm.2020.07.017